2021
DOI: 10.3389/fcimb.2021.767944
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Prebiotic D-Tagatose for Prevention of Oral Disease

Abstract: Recent studies have shown phenotypic and metabolic heterogeneity in related species including Streptococcus oralis, a typical oral commensal bacterium, Streptococcus mutans, a cariogenic bacterium, and Streptococcus gordonii, which functions as an accessory pathogen in periodontopathic biofilm. In this study, metabolites characteristically contained in the saliva of individuals with good oral hygiene were determined, after which the effects of an identified prebiotic candidate, D-tagatose, on phenotype, gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The decreased pH and demineralization of dental tissues lead to the attachment of pathogens to the enamel and cause dental caries [ 50 ]. The acid produced by biofilms damage teeth enamel and lead to the cavitation and destruction of teeth [ 51 ]. Approximately 60–90% incidence of dental caries is observed in underprivileged children due to the acid produced by S. mutans biofilms.…”
Section: Clinically Relevant Human Polymicrobial Biofilm Infectionsmentioning
confidence: 99%
“…The decreased pH and demineralization of dental tissues lead to the attachment of pathogens to the enamel and cause dental caries [ 50 ]. The acid produced by biofilms damage teeth enamel and lead to the cavitation and destruction of teeth [ 51 ]. Approximately 60–90% incidence of dental caries is observed in underprivileged children due to the acid produced by S. mutans biofilms.…”
Section: Clinically Relevant Human Polymicrobial Biofilm Infectionsmentioning
confidence: 99%
“…D-tagatose, a non-cariogenic sugar, is a potential prebiotic that offers lower calories and a lower glycemic index than sucrose 137 . Notably, the saliva of individuals with good oral health is rich in D-tagatose 138 . D-tagatose may inhibit the growth of S. mutans and S. gordonii by affecting glycolysis and its downstream metabolism, but it does not affect S. oralis 138 .…”
Section: Prebioticsmentioning
confidence: 99%
“…Notably, the saliva of individuals with good oral health is rich in D-tagatose 138 . D-tagatose may inhibit the growth of S. mutans and S. gordonii by affecting glycolysis and its downstream metabolism, but it does not affect S. oralis 138 . Encouragingly, chewing gum containing D-tagatose has been shown to inhibit the growth of S. mutans 139 .…”
Section: Prebioticsmentioning
confidence: 99%
“…It is suggested that BAR-encapsulated NPs provide a potent platform to inhibit (prevent) and disrupt (treat) P. gingivalis/S.gordonii biofilms, relative to free BAR [15] . Experimental results demonstrated that D-tagatose found in saliva selectively inhibits the growth of oral pathogens S. mutans and S. gordonii [16] . Similarly, SCFA could be an effective anti-biofilm agent against S. gordonii for the prevention of oral diseases [17] .…”
Section: Treatmentmentioning
confidence: 99%